2005
DOI: 10.1038/sj.bjp.0706199
|View full text |Cite
|
Sign up to set email alerts
|

D‐Aspartate and NMDA, but not L‐aspartate, block AMPA receptors in rat hippocampal neurons

Abstract: 1 The amino acid, D-aspartate, exists in the mammalian brain and is an agonist at the N-methyl-Daspartate (NMDA) subtype of ionotropic glutamate receptors. Here, for the first time, we studied the actions of D-aspartate on a-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate receptors (AMPARs) in acutely isolated rat hippocampal neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Activation of AMPA receptors by its cognate agonist or Group I metabotropic glutamate receptors with DHPG failed to stimulate GLUT1. In contrast, D-aspartate, a substrate of the Na 1 -glutamate cotransporter that does not stimulate AMPA receptors or metabotropic glutamate receptors (Gong et al, 2005;Huang et al, 2005), effectively stimulated GLUT1. With D-aspartate, (71 6 5)% of the cells responded with a significant increase in hexose uptake (n 5 48 cells in six experiments), stimulation which was often stronger than that achieved with glutamate (for example compare Figs.…”
Section: -Glutamate Cotransporter Mediates the Stimulation Of Glut1mentioning
confidence: 89%
“…Activation of AMPA receptors by its cognate agonist or Group I metabotropic glutamate receptors with DHPG failed to stimulate GLUT1. In contrast, D-aspartate, a substrate of the Na 1 -glutamate cotransporter that does not stimulate AMPA receptors or metabotropic glutamate receptors (Gong et al, 2005;Huang et al, 2005), effectively stimulated GLUT1. With D-aspartate, (71 6 5)% of the cells responded with a significant increase in hexose uptake (n 5 48 cells in six experiments), stimulation which was often stronger than that achieved with glutamate (for example compare Figs.…”
Section: -Glutamate Cotransporter Mediates the Stimulation Of Glut1mentioning
confidence: 89%
“…Our earlier report demonstrated that D-aspartate was able to competitively block AMPARs in hippocampal neurons (Gong et al 2005), whereas L-aspartate was virtually free of blocking action. Here we observed similar actions of Dserine and L-serine on AMPARs in the same type of neurons.…”
Section: Other D-amino Acids Also Exhibit Inhibitory Effect On Ampa Rmentioning
confidence: 99%
“…Neurons in CA1 area were isolated from hippocampal slices taken from 2-to 5-week postnatal Sprague-Dawley rats as described previously (Bai et al 2002;Gong et al 2005). Briefly, the rats were anesthetized with halothane and decapitated.…”
Section: Acute Isolation Of Hippocampal Neurons and Whole-cell Patch mentioning
confidence: 99%
“…␣-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid, Kainate, and ␦ Receptor Agonists Glutamate activates all AMPA and kainate receptors by binding within the cleft between domains D1 and D2 of the LBD to induce domain closure. Neither NMDA nor L-aspartate can activate the non-NMDA receptors, and D-aspartate acts as a low-affinity competitive antagonist for native AMPA receptors (Gong et al, 2005). In the structure of the glutamate-bound GluA2 LBD (Fig.…”
Section: Agonist and Antagonist Pharmacologymentioning
confidence: 99%